Control measures to prevent Coronavirus disease 2019 pandemic in endoscopy centers: Multi‐center study. Issue 6 (3rd September 2020) - Huang, Qing; Liu, Guanyi; Wang, Jiewei; Duan, Tianjiao; Feng, Yun; Lin, Xiaoqing; Zhu, Yuanmin; Wang, Huihui; Cui, Yi; He, Shuixiang; Zhu, Yunqing; Li, Peng; et al.
Abstract : Aims: To investigate control measures for COVID‐19 pandemic in GIE centers in China. Methods: This is a retrospective multi‐center research, including seven centers. Data collection was from 1 February to 31 March 2020 and the same period in 2019. Results: There were a total of 28 COVID‐19 definite cases in these hospitals. Six out of seven GIE centers were arranged to shut down on 1 February, with a mean number of shutdown days of 23.6 ± 5.3. The actual workloads were only 10.3%–62.9% compared to those last year. All centers had a preoperative COVID‐19 screening process. Epidemiological questionnaire, temperature taking and QR‐code of journey were conducted. Chest CT scan was conducted during the shutdown period and continued in five centers after return to work. Antibody and nucleic acid test were applied in one to three centers. All endoscopists had advanced PPE. Five centers used surgical mask and the rest used N95 mask. Six centers used goggles or face shield. Five centers selected isolation gowns and the rest selected protective suits. The change frequency of these PPE was 4 h. Sterilizing measures were improved in six centers. Five centers utilized ultraviolet and six centers strengthened natural ventilation. Four and six centers used peracetic acid during the period of shutdown and return to work, alone or matched with OPA or acidified water. Conclusions: Many effective control measures were conducted in GIE centers during the outbreak, including patients' volume limitation, preoperative COVID‐19 screening, advanced PPE and disinfection methods.